2019
DOI: 10.1029/2018jf004778
|View full text |Cite
|
Sign up to set email alerts
|

The Geomorphic Impact of Outburst Floods: Integrating Observations and Numerical Simulations of the 2000 Yigong Flood, Eastern Himalaya

Abstract: Outburst floods in mountainous landscapes traverse complex topography and interact with the channel and valley walls, producing intense flow hydraulics that drive geomorphic change and impact people and infrastructure. Evidence of modern and ancient outburst floods is scattered around the eastern Himalaya, but hydraulics related to these geomorphic features are uncharacterized, limiting our understanding of the role of large floods in long‐term evolution of the region. Here we combine remote and field observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 120 publications
(223 reference statements)
2
99
0
Order By: Relevance
“…Cenderelli and Wohl (2001) and Fort et al (2010) compared seasonal high flow floods (SHFFs) with discharges of recent GLOF and LLOF events and they appeared to be at least one order of magnitude higher than monsoonal precipitation peak discharges in central Himalayan catchments (Kali Gandaki and Mount Everest region). Peak discharges reaching 10 5 m 3 /s have been documented or suggested for a few historical events in the Himalaya mainly associated to LLOF such as the Great Indus flood of 1841 (Mason, 1929;Shroder et al, 1991), the great outburst in April 2000 in the Tibetan Yigong Zangbo River (Shang et al, 2003;Delaney and Evans, 2015;Turzewski et al, 2019), and the large LLOFs at Dadu River and Yalong https://doi.org/10.5194/esurf-2020-17 Preprint. Discussion started: 20 March 2020 c Author(s) 2020.…”
Section: Paleo-discharge Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cenderelli and Wohl (2001) and Fort et al (2010) compared seasonal high flow floods (SHFFs) with discharges of recent GLOF and LLOF events and they appeared to be at least one order of magnitude higher than monsoonal precipitation peak discharges in central Himalayan catchments (Kali Gandaki and Mount Everest region). Peak discharges reaching 10 5 m 3 /s have been documented or suggested for a few historical events in the Himalaya mainly associated to LLOF such as the Great Indus flood of 1841 (Mason, 1929;Shroder et al, 1991), the great outburst in April 2000 in the Tibetan Yigong Zangbo River (Shang et al, 2003;Delaney and Evans, 2015;Turzewski et al, 2019), and the large LLOFs at Dadu River and Yalong https://doi.org/10.5194/esurf-2020-17 Preprint. Discussion started: 20 March 2020 c Author(s) 2020.…”
Section: Paleo-discharge Estimatesmentioning
confidence: 99%
“…Costa and Schuster 1988;Cenderelli, 2000;O'Conner and Beebee, 2009;Korup and Tweed, 2007;Wohl, 2013;Cook et al, 2018). LOFs represent both a significant hazard (Kattelmann, 2003; and an active geomorphic agent of landscape evolution (Wohl, 2013;Cook et al, 2018;Turzewski et al, 2019).…”
mentioning
confidence: 99%
“…A total of 882 high-mountain lakes were identified by Emmer et al (2016). Some of these lakes are susceptible to GLOFs (Vilímek et al, 2005;Vilímek, 2013, 2014;ANA, 2014;Iturrizaga, 2014). A total of 28 geomorphologically effective GLOFs originating from moraine-dammed lakes have been documented (Emmer, 2017).…”
mentioning
confidence: 99%
“…Lang et al (2013) studying undated flood deposits of the Siang, and using U-Pb zircon ages to determine sediment provenance, suggested that floods facilitate sediment erosion from the Namche Barwa syntaxis zone. Turzewski et al (2019), in investigating sediments laid down by the 2000 flood, suggested that sediment was mainly generated from the Tibetan plateau; and the fast exhuming Namche Barwa syntaxis zone was the secondary source. Our study suggests the occurrence of two types of floods in the Siang valley: (i) episodic lake outburst megafloods that deposit massive sand piles along the channel, for example as observed at Pangin, Geku, Yinkiong, Bombao and Tuting; and (ii) floods caused by a strong southwest monsoon that produced meter-scale sand-silt couplets, for example as observed in the sequence at Ranaghat.…”
Section: Discussionmentioning
confidence: 99%